Stacked Abdominal Flap for Unilateral Breast Reconstruction - Murray, Alexandra; Wasiak, Jason; Rozen, Warren Matthew; Ferris, Scott; Grinsell, Damien (Journal of Reconstructive Microsurgery, 2015)
Background The abdominal flap can be used in a stacked, double-pedicle configuration for unilateral breast reconstruction. Aided by preoperative mapping, this is a good option when a single-pedicle flap is deemed unsuitable. We present reliable outcomes using the stacked flap and a logical classification system for its use.Methods From 2008 to 2013, 18 patients underwent a stacked abdominal flap for unilateral breast reconstruction. Flaps utilized deep inferior epigastric (D) and superficial inferior epigastric (S) pedicle combinations. Preoperative computed tomography angiogram was performed on all patients. Medical records were reviewed for complications and clinical data, and a thorough clinical evaluation was performed on all patients at follow-up. Flaps were all double-pedicled, with the secondary pedicle anastomosed onto the primary pedicle (type 1 to 3) or onto a second recipient vessel (type 4). Flaps were then classified into groups, based on pedicle dominance and intraflap anastomosis.Results Twelve reconstructions were immediate and six delayed. Mean operative time was 7 hours, the most frequently used configuration being a type 1 DD, that is, secondary pedicle (D) anastomosed end-to-end onto the superior continuation of the primary pedicle (D). Average hospital stay was 6 days. There were no flap losses and minimal complications, and mean follow-up was 20 months.Conclusion Use of this flap poses a greater challenge to the microsurgical breast reconstruction. We demonstrate its reliable use in women deemed unsuitable for a single-pedicle flap. Our structured system clarifies vascular options, and preoperative perforator mapping tools are essential to the success of this technique.
Keywords: breast; stacked; DIEP; reconstruction; classification